Fate of the molar dental lamina in the monophyodont mouse - Dosedělová, Hana; Dumková, Jana; Lesot, Hervé; Glocová, Kristýna; Kunová, Michaela; Tucker, Abigail S; Veselá, Iva; Krejčí, Pavel; Tichý, František; Hampl, Aleš; Buchtová, Marcela (PloS one, 2015)
The successional dental lamina (SDL) plays an essential role in the development of replacement teeth in diphyodont and polyphyodont animals. A morphologically similar structure, the rudimental successional dental lamina (RSDL), has been described in monophyodont (only one tooth generation) lizards on the lingual side of the developing functional tooth. This rudimentary lamina regresses, which has been proposed to play a role in preventing the formation of future generations of teeth. A similar rudimentary lingual structure has been reported associated with the first molar in the monophyodont mouse, and we show that this structure is common to all murine molars. Intriguingly, a lingual lamina is also observed on the non-replacing molars of other diphyodont mammals (pig and hedgehog), initially appearing very similar to the successional dental lamina on the replacing teeth. We have analyzed the morphological as well as ultrastructural changes that occur during the development and loss of this molar lamina in the mouse, from its initiation at late embryonic stages to its disappearance at postnatal stages. We show that loss appears to be driven by a reduction in cell proliferation, down-regulation of the progenitor marker Sox2, with only a small number of cells undergoing programmed cell death. The lingual lamina was associated with the dental stalk, a short epithelial connection between the tooth germ and the oral epithelium. The dental stalk remained in contact with the oral epithelium throughout tooth development up to eruption when connective tissue and numerous capillaries progressively invaded the dental stalk. The buccal side of the dental stalk underwent keratinisation and became part of the gingival epithelium, while most of the lingual cells underwent programmed cell death and the tissue directly above the erupting tooth was shed into the oral cavity.
Keywords: moláry; apoptóza; ústní sliznice; transkripční faktory SOXB1; Embryo, Mammalian; Animals; Hedgehogs; Mouth Mucosa; Swine; embryo savčí; SOXB1 Transcription Factors; Molar; prasata; myši; zvířata; Apoptosis; Mice; ježkovití